Race, Ethnicity, Gender, and Home Planet: The “Other” in Robert Heinlein’s Juvenile Science Fiction - Sullivan III, C. W. (Hungarian Journal of English and American Studies, 2021)
This essay examines Heinlein's Young Adult (YA) stories—commonly referred to as his “juveniles”—and argues that Heinlein's "Others" are not defined by race, gender, or planet of origin but by their inability to understand and deal with the changes that inter-planetary travel will bring. (CWS)